Toward zero-defect programming - Stavely, Allan M (Addison-Wesley, 1999)
Toward Zero-Defect Programming describes current methods for writing (nearly) bug-free programs. These methods are based on practices developed at IBM and elsewhere under the name Cleanroom Software Engineering. The successful application of these methods in commercial projects over the past fifteen years has produced defect rates that are, at least, an order of magnitude lower than industry averages. Remarkably, this reduction in defects comes at no net cost; on the contrary, it is often accompanied by increased productivity and shorter overall development time. In a concise and well-illustrated presentation, Stavely shows how these methods can be applied in three key areas of software development: 1. specification, 2. verification, and 3. testing.